Wall Effect Analysis in Thermal-Hydraulics Aspect of HTR-10 and PR-3000 Reactors Using Different Porosity Models - Bilal El Bari; Dwi Irwanto (Science and Technology Indonesia, 2021)
Gen-IV is the latest generation of a nuclear reactor with better aspects than the previous generation, Pebble-Bed Reactor (PBR) is one of them. PBR using spherical shape fuel or known as pebble fuel. Hence, the physical things that are happening in the core are significantly different from the reactor using a fuel pin. Often the reactor core is assumed as a porous medium because of the void within the pebble fuel. The coolant that moves in the core can be carried as a fluid that flows through a porous medium. The thermal-hydraulics aspect is one of the significant aspects that must have been considered in every nuclear fission reactor because it is closely related to reactor safety. The wall effect happened in a packed bed, making the porosity near-wall position higher than other positions. The porosity value can induce the coolant flow, known as wall channeling, which can influence thereactor’s thermal-hydraulics aspect. In this study, thermal-hydraulics analysis for PBR is performed, and the wall effect is taken into account in the calculations. A thermal-hydraulic code, namely mPEBBLE, was developed based on the PEBBLE code to include the wall effect in the calculation. The code is based on the finite-difference method with axisymmetric cylinder geometry (R-Z) that consists of 4 primary equations; stream flow, pressure recovery, solid energy balance, and thermal energy balance. The analysis was performed for HTR-10 and PR-3000, two PBR-type reactors with different reactor core sizes. The results conclude that the larger bed as in PR-3000 is undergoing a smaller effect caused by the wall effect than in the smaller bed, such as the HTR-10. Comparison of three porosity models, Vortmeyer-Schuster, Mueller, and Benenati-Borislow, to the wall channeling, were also taken into accountin the present study.